Comparative analysis of Hmx expression and the distribution of neuronal somata in the trigeminal ganglion in lamprey and shark: insights into the homology of the trigeminal nerve branches and the evolutionary origin of the vertebrate jaw - Tamura, Motoki; Ishikawa, Ryota; Nakanishi, Yuki; Pascual-Anaya, Juan; Fukui, Makiko; Saitou, Takashi; Sugahara, Fumiaki; Rijli, Filippo M.; Kuratani, Shigeru; Suzuki, Daichi G.; Murakami, Yasunori (BMC, 2023)
The evolutionary origin of the jaw remains one of the most enigmatic events in vertebrate evolution. The trigeminal nerve is a key component for understanding jaw evolution, as it plays a crucial role as a sensorimotor interface for the effective manipulation of the jaw. This nerve is also found in the lamprey, an extant jawless vertebrate. The trigeminal nerve has three major branches in both the lamprey and jawed vertebrates. Although each of these branches was classically thought to be homologous between these two taxa, this homology is now in doubt. In the present study, we compared expression patterns of Hmx, a candidate genetic marker of the mandibular nerve (rV3, the third branch of the trigeminal nerve in jawed vertebrates), and the distribution of neuronal somata of trigeminal nerve branches in the trigeminal ganglion in lamprey and shark. We first confirmed the conserved expression pattern of Hmx1 in the shark rV3 neuronal somata, which are distributed in the caudal part of the trigeminal ganglion. By contrast, lamprey Hmx genes showed peculiar expression patterns, with expression in the ventrocaudal part of the trigeminal ganglion similar to Hmx1 expression in jawed vertebrates, which labeled the neuronal somata of the second branch. Based on these results, we propose two alternative hypotheses regarding the homology of the trigeminal nerve branches, providing new insights into the evolutionary origin of the vertebrate jaw.
Keywords: Mandíbula - Evolución; Nervio trigémino; Lamprey; Shark; Trigeminal nerve; Craniofacial development; Evolution